Risk Assessment of aGas Well Test in the South China SeaBased on Fault Tree Analysis (International Journal of Scientific Research and Management (IJSRM), 2020)
Deepwater gas well testing in the South China Sea is characterized by high difficulty, high investment and high risk. In order to reduce effectively the risk of the gas well testing operation in the South China Sea, the potential risk factors in the South China Sea deepwater testing operation were analyzed and 42 categories of risk factors were identified. The fault tree analysis method was used to establish the fault tree model for a deepwater testing operation in a South China Sea gas well, and analyze the inter restricted relationship between risks. Combining with the hierarchical analysis method to calculate the weight values of the risk evaluation indicators and use the product of it with probability importance as the corrected value for the probability of occurrence of the basic event in the fault tree model, the fault tree analysis was performed to determine the probability of occurrence of the top-level event. The results of the study help reduce the risk of accidents in deepwater gas well testing operations and can inform the management of deepwater gas well testing sites.